The educational practices in technical schools of the Province of Neuquén: experiences about the criteria of “justice” in the access (Praxis Educativa, 2022)
In this article we analyze the selection criteria of the educational practices carried out by students of technical schools and the points of tension that prevail when experiencing it, both by students and by teachers. We state that the criteria of justice are the drivers in the senses deployed by institutional actors, either from the informality of the proposal (in cases where they are not mandatory) or from the effects of its institutionalization (the practice that remains framed in the curriculum proposal). The article is based on a case study in three technical schools, from a qualitative approach based on the analysis of interviews and focus groups with students and teachers.
Keywords: educational practices; technical schools; justice criteria; internships; training for work